The Assessment of Legal Knowledge among Obstetricians and Gynecologists about Legal Consequences of Assisted Reproductive Techniques: Legal Knowledge about Legal Consequences of Assisted Reproductive Techniques - Mohseni , Tara; Chaichian , Shahla; Mohseni , Mohammad; Moazzami , Bahram (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: With the emergence and proliferation of assisted reproductive techniques, the needs of societies have altered. Therefore, measuring the level of legal awareness of gynecologists and obstetricians as the primary consultants of infertile couples can be significantly influential. In this study, we aimed to provide insight into the lack of legal knowledge of this group of specialists, which undermines the quality of healthcare services. Materials and Methods: This cross-sectional study was conducted among 80 gynecologists and obstetricians in Tehran, Iran, in 2016. We used a 26-item questionnaire on the common legal challenges of infertile couples. Ethical Considerations: Verbal informed consent of the participants was obtained after explaining the purpose of the study and the positive consequences of enhancing medical education and improving the doctor-patient relationship. Findings: In general, 30% of the participants were male and 70% were female (age range: 35-75 years). Further, 24% of the participants did not respond to the questionnaire due to limited or lack of knowledge, and 28% knew the permitted types of artificial insemination by Iran’s laws. Concerning the basic rights of the child, 17% provided the correct response, and regarding the parental rights, 4% were aware of the existing legal condition. Finally, on the subject of surrogacy contracts, 22% were cognizant of the critical basics. Conclusion: Based on the mentioned results and due to the deep gap between the fields of law and medicine, improvement of the existing curriculum in Iran is highly recommended. *Corresponding Author: Tara Mohseni; Email: taara.mohseni@gmail.com; ORCID: https://orcid.org/0000-0003-2704-0689 Please cite this article as: Mohseni T, Chaichian Sh, Mohseni M, Moazzami B. The Assessment of Legal Knowledge among Obstetricians and Gynecologists about Legal Consequences of Assisted Reproductive Techniques. Bioeth Health Law J. 2021; 1:1-6 (e21). http://doi.org/10.22037/bhl.v1i1.38180